KONTRIBUSI PENGASUH TERHADAP HAFALAN AL-QUR’AN MELALUI METODE TASMI’ KELIPATAN 5 DI PONDOK PESANTREN ROBITHOTUL ISLAM KREJENGAN - Nur Izza Kamila; Kustiana Arisanti; Nur Hayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Tahfidz Islamic boarding schools play an important role in producing a generation of Qur'an memorizers who not only possess extensive memorization but also maintain the strength and quality of their memorization. The success of students in memorizing the Qur'an cannot be separated from the contribution of caregivers in guiding, supervising, and evaluating the tahfidz learning process. One of the methods implemented to maintain the quality of memorization is the multiple-of-five tasmi’ method. This study aims to determine the contribution of caregivers to the success of students' Qur'an memorization through the implementation of the multiple-of-five tasmi’ method at Robithotul Islam Krejengan Islamic Boarding School. This study employed a descriptive qualitative approach with a case study research design. Data collection techniques were conducted through observation, interviews, and documentation involving boarding school caregivers, tahfidz teachers, and tahfidz students as research subjects. The results showed that caregivers’ contributions significantly influenced the success of students' memorization, particularly in controlling the implementation of tasmi’, enforcing discipline, providing motivation, and assessing the fluency and accuracy of students' memorization. The multiple-of-five tasmi’ method was proven to help students maintain memorization strength, improve mental readiness, and minimize recitation errors. Supporting factors include caregiver consistency, student commitment, and a conducive boarding school environment, while inhibiting factors include differences in students' abilities and mental pressure during tasmi’ sessions in one sitting. It can be concluded that caregivers play an important role in the success of students' Qur'an memorization through the implementation of this method.